Promoting transcriptome diversity - L. Strausberg, Robert; Levy, Samuel (Genome Research, 2007)
Although the number of protein-encoding human genes is more limited than many had estimated, the human transcript repertoire is much more diverse than anticipated. In part, transcript diversity is generated through the use of alternative promoters and alternate splicing. In addition, based on discoveries using technologies such as full-length cDNA libraries and whole genome tiling microarrays, it is now likely that non-protein-encoding transcripts comprise a substantial fraction of the human RNA population. Much attention is currently focused on understanding the role of alternative promoters in generating transcript diversity, both for non-protein-encoding (ncRNAs) and protein-encoding RNAs.